2019
DOI: 10.14710/jbtr.v5i1.3711
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria Parasites among Pregnant Women and Children under Five years in Ekiti State, Southwest Nigeria.

Abstract: Background: Malaria is a deadly disease causing serious public health issues among pregnant women and children worldwide especially in tropical and subtropical Africa. This study was carried out to determine the prevalence of malaria parasites among pregnant women and children under five years in Ekiti State, Nigeria.Methodology: A total of 380 blood samples were collected from the pregnant women and children under five years respectively. Malaria parasites were examined microscopically on thick and thin blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
8
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 5 publications
6
8
3
Order By: Relevance
“…Indeed, the high malaria parasite prevalence recorded in this study was also similar to the reports of previous studies in other parts of Nigeria (Greenwood et al, 2005;Asaolu & Igbaakin, 2009;Okonko et al, 2009;Iwueze et al, 2014;Ayogu et al, 2016;Umma et al, 2017;Awosolu et al, 2019Awosolu et al, , 2020. However, malaria parasite prevalence in this study is greater than studies reported by Nzeako et al (2013), Udoh et al (2013) and Simon-Oke et al (2019). The high malaria parasite prevalent in this current study can be attributed to the multifaceted prevailing environmental factors such as temperature, rainfall and forest cover which provide good breeding system for the mosquito vector.…”
Section: Discussioncontrasting
confidence: 66%
“…Indeed, the high malaria parasite prevalence recorded in this study was also similar to the reports of previous studies in other parts of Nigeria (Greenwood et al, 2005;Asaolu & Igbaakin, 2009;Okonko et al, 2009;Iwueze et al, 2014;Ayogu et al, 2016;Umma et al, 2017;Awosolu et al, 2019Awosolu et al, , 2020. However, malaria parasite prevalence in this study is greater than studies reported by Nzeako et al (2013), Udoh et al (2013) and Simon-Oke et al (2019). The high malaria parasite prevalent in this current study can be attributed to the multifaceted prevailing environmental factors such as temperature, rainfall and forest cover which provide good breeding system for the mosquito vector.…”
Section: Discussioncontrasting
confidence: 66%
“…There was no significant difference in the distribution of positive tests by microscopy and RDT among the sample population (chi-square = 2.60, p = 0.106) [17] and 63% in a 2019 study in Ekiti State [18]. These studies all used microscopy for parasite detection.…”
Section: Fig 1 Distribution Of Microscopy and Rdt Resultsmentioning
confidence: 93%
“…Similar to findings from another study in the North West region of Cameroon [35], the young adult age group is more at risk of malaria. Although children < 5 years and pregnant women are naturally more predisposed to malaria [36][37][38][39], differences in exposure patterns may also increase the risk of malaria among young adults. Compared to other age groups, young adults are more involved in outdoor activities like farming and could be casual towards malaria preventive measures.…”
Section: Discussionmentioning
confidence: 99%